Benchmarks : new and selected poems 1963-2013 - Dauenhauer, Richard (Alaska literary series., 2013)
Russian, German, Tlingit. Like the languages he translates, Richard Dauenhauer's poetry offers unexpected surprises. A prolific translator who also works in Finnish, Swedish, and classical Greek, he has a poetic command of language that has earned him wide recognition over fifty years of published work. Benchmarks spans these decades of writing, and each poem contained within marks a certain place in time and space, like a surveyor's benchmark. The poems play with language while focusing on the land and people of Alaska. And like Alaska itself, this book offers a variety of delights-readers wi.